2017
DOI: 10.7199/ped.oncall.2017.s1
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Knowledge, Attitudes and Beliefs Regarding Sun Protection in Children: A Qualitative Study

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It also sets the scene for potential further qualitative studies aiming to develop prevention strategies to reduce the high risk of KC among farmers. Studies looking at factors associated with the use of primary prevention of KC have shown that the decision for or against sun protection represents a complex behaviour determined by a range of different factors . Here we have shown that knowledge and perception of KC and UVR, individually perceived barriers to using sun protection, individual experiences with sunburn and skin cancer, as well as farm life‐specific circumstances, are factors in the decision to apply or not to apply sun‐protection measures.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…It also sets the scene for potential further qualitative studies aiming to develop prevention strategies to reduce the high risk of KC among farmers. Studies looking at factors associated with the use of primary prevention of KC have shown that the decision for or against sun protection represents a complex behaviour determined by a range of different factors . Here we have shown that knowledge and perception of KC and UVR, individually perceived barriers to using sun protection, individual experiences with sunburn and skin cancer, as well as farm life‐specific circumstances, are factors in the decision to apply or not to apply sun‐protection measures.…”
Section: Discussionmentioning
confidence: 70%
“…Negative experiences such as having a family member or friend with skin cancer or personally having suffered from severe sunburns seems to have strongly influenced the perceived need of sun protection. Farmers without respective experiences and typically underestimating the need for sun protection in this study therefore might be led by ‘unrealistic optimism’, as described in previous studies . This may point to the importance of narrative storytelling to convey information on the prevention of KC in farmers …”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Interviews averaged 15 minutes in length with a range of 9 to 31 minutes, and were conducted by a research assistant (MO). Interviews followed a semi‐structured format, allowing the interviewer to ensure key questions and issues were covered while also having flexibility to discuss topics introduced by participants . All interviews were audio recorded and professionally transcribed verbatim by an external source.…”
Section: Methodsmentioning
confidence: 99%